2006
DOI: 10.1126/science.1135347
|View full text |Cite
|
Sign up to set email alerts
|

Biomass, Size, and Trophic Status of Top Predators in the Pacific Ocean

Abstract: Fisheries have removed at least 50 million tons of tuna and other top-level predators from the Pacific Ocean pelagic ecosystem since 1950, leading to concerns about a catastrophic reduction in population biomass and the collapse of oceanic food chains. We analyzed all available data from Pacific tuna fisheries for 1950-2004 to provide comprehensive estimates of fishery impacts on population biomass and size structure. Current biomass ranges among species from 36 to 91% of the biomass predicted in the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
139
1
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(151 citation statements)
references
References 16 publications
5
139
1
6
Order By: Relevance
“…Notwithstanding the gross differences, both studies agree on the steep declines of three bluefin populations and one albacore population, which are clearly overfished with current biomasses below B MSY . Instead, our results present a wide range of trajectories across tuna populations, which are more consistent with the findings of a study by Sibert et al (3), which reports declines ranging from 11-88% from baseline adult biomass across the Pacific tuna populations. Moreover, our findings are consistent with those of a recent evaluation of the global conservation status of scombrid species carried out by the International Union for Conservation of Nature (IUCN), which showed that 68% (35 of 61 species) of scombrids are not considered to be threatened with extinction but that a few (5 species) have declined sufficiently to trigger listing under the IUCN Red List Threatened categories, notably the Southern and Atlantic bluefin tunas (22).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Notwithstanding the gross differences, both studies agree on the steep declines of three bluefin populations and one albacore population, which are clearly overfished with current biomasses below B MSY . Instead, our results present a wide range of trajectories across tuna populations, which are more consistent with the findings of a study by Sibert et al (3), which reports declines ranging from 11-88% from baseline adult biomass across the Pacific tuna populations. Moreover, our findings are consistent with those of a recent evaluation of the global conservation status of scombrid species carried out by the International Union for Conservation of Nature (IUCN), which showed that 68% (35 of 61 species) of scombrids are not considered to be threatened with extinction but that a few (5 species) have declined sufficiently to trigger listing under the IUCN Red List Threatened categories, notably the Southern and Atlantic bluefin tunas (22).…”
Section: Discussionsupporting
confidence: 82%
“…Fifty or more years later, the global impact of fishing on pelagic fishes and their ecosystems is only now beginning to be understood (3,4). Tunas and their relatives, which include 51 species of tunas, Spanish mackerels, bonitos, and mackerels (collectively known as scombrids), are major components of pelagic ecosystems, being both important predators and forage species that are widely distributed throughout the temperate and tropical epipelagic waters of the world's oceans (Table S1).…”
mentioning
confidence: 99%
“…iii) Fishery impact is the percentage of the adult biomass in the absence of fishing that is removed by fishing under some fishery management scenario (3,15), 100 1 − Byi ByF=0 , where B yi is the average adult biomass in the final year, y, of the simulation under scenario i, and B yF=0 is the average adult biomass in year y when fishing mortality is set to zero (scenario 9, F = 0; Table 1). Fishery impact is a convenient measure of stock depletion.…”
Section: Fishery Management Scenarios and Evaluation Metricsmentioning
confidence: 99%
“…In addition to performing critical ecosystem services such as global climate regulation, the CNP pelagic ecosystem houses large-scale commercial fisheries that target high-value tuna and billfish species (He et al 1997, Bigelow et al 2002, Sibert et al 2006. Persistent harvest of predatory fish biomass has imparted measurable changes to CNP pelagic ecosystem structure, while environmental variability has also been reported to affect predatory fish populations and fishery removal patterns in recent decades (Doney et al 2012).…”
Section: Introductionmentioning
confidence: 99%